THE EFFECT OF PARENT ATTENTION AND STUDENT’S INDEPENDENCE ON LEARNING ACHIEVEMENT IN ECONOMIC LESSONS AT SMAN 1 GAROGA - Pardosi, Anita; Matondang, Khairani Alawiyah; Indriani, Riza; Triansyah, Agus Fadly (Proceeding of International Conference on Islamic Education (ICIED); Vol 6 No 1 (2021): Proceeding of International Conference on Islamic Education (ICEID), 2021)
This study aims to analyze the effect of parental attention and student independence on learning achievement in economics subjects for class XI IPS students in the online learning model. The research location is in SMA Negeri 1 Garoga. The instrument used to measure parental attention and student independence was in the form of a questionnaire distributed using google form and distributed to 100 respondents. The data analysis technique used is multiple linear regression analysis. Data processing using SPSS 20 application. Based on the results of data analysis obtained from multiple linear regression equations, there is a positive and significant influence between parental attention and student independence on student achievement. Therefore, it is necessary to pay attention to parents to increase students' independence in achieving optimal learning achievement improvements.